2014
DOI: 10.1039/c4cp00574k
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of biomedical silver-doped phosphate-based glasses from molecular dynamics simulations

Abstract: First-principles and classical molecular dynamics simulations of undoped and silver-doped phosphate-based glasses with 50 mol% P2O5, 0-20 mol% Ag2O, and varying amounts of Na2O and CaO have been carried out. Ag occupies a distorted local coordination with a mean Ag-O bond length of 2.5 Å and an ill-defined first coordination shell. This environment is shown to be distorted octahedral/trigonal bipyramidal. Ag-O coordination numbers of 5.42 and 5.54-5.71 are calculated for first-principles and classical methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 50 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…To perform the classical simulations, we have developed a new interatomic potential, which takes account of the polarizability of the oxygen ions. Our previous work [28][29][30] on the dissolution of phosphate glasses had shown us that the number of phosphate chains chemically bound to each network modifier is a key parameter to understand the associated effect on the dissolution. We have found that strontium bonds to a similar number of phosphate chains as calcium does.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform the classical simulations, we have developed a new interatomic potential, which takes account of the polarizability of the oxygen ions. Our previous work [28][29][30] on the dissolution of phosphate glasses had shown us that the number of phosphate chains chemically bound to each network modifier is a key parameter to understand the associated effect on the dissolution. We have found that strontium bonds to a similar number of phosphate chains as calcium does.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations provide the atomic structure of the glass, as well as enabling computation of large-scale materials properties. We and others have previously used MD simulations to elucidate the connection between atomic structure and dissolution behaviour of a variety of silicate [20][21][22][23][24][25][26][27] and phosphate glasses [28][29][30] intended for implantation, including strontium-containing silicate glass [13,14]. However, there have been no simulations of Sr in phosphate glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is then cooled, usually by reducing the temperature in steps, before the production run is performed at room temperature. First-principles molecular dynamics and the melt-andquench method have been used to prepare glass models whose structural properties are in agreement with experiment for silicate [34,35], phosphate [36][37][38] and metallic [22,[39][40][41] glasses.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of silver inclusion on PBG structure and dissolution is covered in two works 37,38 . The first of these reports simulation results of metaphosphate (50 mol % P 2 O 5 ) glass compositions, in which Na 2 O (sodium field strength = 0.19 e/Å 2 ) and Ag 2 O (with a very similar field strength) are substituted for one another to maintain network connectivity.…”
Section: Silvermentioning
confidence: 99%